Perbandingan Sistem Pemerintahan Indonesia Menurut UUD 1945 Asli dan Setelah Amandemen: Implikasi Terhadap Pembagian Kekuasaan dan Prinsip Checks And Balances - Daniel Reynaldi L Tobing; Wilma Silalahi (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study examines the comparison of Indonesia’s governmental system before and after the amendments to the 1945 Constitution of the Republic of Indonesia (UUD 1945), focusing on the distribution of powers among the executive, legislative, and judicial branches, as well as the implementation of the checks and balances principle in state governance. Prior to the amendments, Indonesia’s system was highly centralized, granting dominant power to the President while limiting the roles of the legislative and judiciary. Through four constitutional amendments between 1999 and 2002, the system evolved toward greater democracy, transparency, and balance. These amendments strengthened the legislative authority of the House of Representatives (DPR), established new institutions such as the Constitutional Court (MK) and the Judicial Commission (KY), and abolished the concept of a supreme state body. The checks and balances principle now serves as the core mechanism preventing power concentration among state institutions. Using a normative juridical approach, this study concludes that the amendments successfully reinforced a more genuine presidential system and upheld popular sovereignty within a democratic constitutional state.